Derivation and assessment of a sex-specific fetal growth standard. (12th December 2022) - Blue, Nathan R.; Allshouse, Amanda A.; Heerboth, Sarah; Grobman, William; Mercer, Brian; Shanks, Anthony; Bregand-White, Julia M.; Simhan, Hyagriv; Reddy, Uma M.; Saade, George; Parry, Samuel; Silver, Robert M.
Abstract: Purpose: To derive a prescriptive sex-specific fetal growth standard and assess clinical management and outcomes according to sex-specific growth status. Materials and methods: This was a secondary analysis of the Nulliparous Pregnancy Outcomes Study: Monitoring Mothers-to-Be (nuMoM2b), a prospective observational study of 10, 038 nulliparas from eight U.S. centers who underwent ultrasounds at 14–20 and 22–29 weeks with outcomes ascertained after delivery. From these, we selected a nested cohort of lower risk participants (excluded those with chronic hypertension, pre-gestational diabetes, suspected aneuploidy, and preterm delivery) to derive a sex-specific equation for expected fetal growth using fetal weights by ultrasound and at birth. We compared the male-female discrepancy in the rate of weight <10th (small for gestational age [SGA]) and >90th (large for gestational age [LGA]) percentiles between the sex-specific and sex-neutral (Hadlock) standards. Using the full unselected cohort, we then assessed outcomes and clinical management according to sex-specific SGA and LGA status. Results: Overall, 7280 infants in the lower risk nested cohort were used to derive a sex-specific equation with fetal sex included as an equation intercept. The sex-neutral standard diagnosed SGA more often in female newborns (21% vs. 13%, p < .001) and LGA more often in male newborns (5% vs. 3%, p < .001). The sex-specific standard resolved these disparities (SGA: 9% vs. 10%, p = .23; LGA: 13% vs. 13%, p = .58). To approximate an unselected population, 1059 participants initially excluded for risk factors for abnormal growth were then included for our secondary objective ( N = 8339). In this unselected cohort, 39% (95% CI 37.0–42.0%) of the 1498 newborns classified as SGA by the sex-neutral standard were reclassified as appropriate for gestational age (AGA) by the sex-specific standard. These reclassified newborns were more likely to be delivered for growth restriction despite having lower risk of morbidity (females) or comparable risk of morbidity (males) compared to newborns considered AGA by both methods. Of the 6485 newborns considered AGA by the sex-neutral standard, 737 (11.4%, 95% CI 10.6–12.2%) were reclassified as LGA by the sex-specific standard. These reclassified newborns had higher rates of cesarean for arrest of descent, cesarean for arrest of dilation, and shoulder dystocia than newborns considered AGA by both methods. None were reclassified from LGA to AGA by the sex-specific standard. Conclusion: The Hadlock sex-neutral standard generates sex disparities in SGA and LGA at birth. Our sex-specific standard resolves these disparities and has the potential to improve accuracy of growth pathology risk stratification.